(untitled) (Journal of Pharmaceutical Negative Results, 2023)
A descriptive analytical study was carried out at Karbala intermediate schools students from February 12/02/2014 to October-2/10/2014 in order to assess the effect of psychological factors on truancy among intermediate schools, to find out the relationship between truancy and demographic characteristics, and to identify the relationship between truancy psychological factors .The present investigation was undertaken to study the psychological factors that cause truancy among adolescent students . A total of 217 students within the age of 12 – 17 years from eight government school in Karbala city . The factors took under consideration personal factors , depression, anxiety, the nature of the curricula , school problems relationship with the teacher, the school atmosphere , family problems , relationship with peers and other, factors that are relevant to work. Reliability of the questionnaire was determined based on the internal consistency of the questionnaire by calculating split-half technique and cronbachs' alpha coefficient, and the validity determined through a panel of (12) experts . The data were described statistical, and analyzed through use of descriptive and inferential statistical analysis procedures . The results revealed that the sample had low-moderate level of self concept , and that the students had moderate level of depressive symptoms. The result also showed that the students had moderate to high level of anxiety ,there were significant differences in wishing to go to school with regard to effect of psychological factors related to textbooks (curriculum ) and related to the teachers and the ways of teaching . The study recommended to follow the method of mutual school respect between the students and educational staff, avoid insult the students whatever the case was, and when it is necessity for punishment there are many other effective non-insulting ways , and continual renewal and development of educational curriculum with educational means to be more accepted instead of daily boring routine